IMPROVING STUDENTS’ ANALYTICAL ESSAY WRITING BASED ON POETRY THROUGH LITERARY RESPONSE APPROACH - Maria Safriyanti (JEE (Journal of English Education), 2016)
Based on the researcher‟s experience and observation, the students analytical essay writing skill at the second year of English education department, class E of UIN Suska Riau still indicated low. It was assumed that this condition was caused by inappropriate teaching process done by the lecturer.The purposes of the research were to explain whether literary response approach could better improve students‟ analytical essay writing skill at the second year of English education department, class e of UIN Suska Riau. The researcher was helped by the collaborator who used the observation checklists, field notes, and the interviews as the research instruments. Besides, she also used analytical essay writing tests to see thestudents‟ improvement of analytical essay writing on each cycle. The research stared on October, 29th, 2008 and ended on 14thof January-2009. The percentage of the average improvement on cycle I for all analytical essay writing components was 54, 25 %. There was the improvement, if it was compared to the previous result at the last semester. It was only 32,35%. At the second cycle, it improved to 61,44 %, and at the end of cycle III improved to 78,43 %.the factors of literary response approach that influenced students‟ analytical essay writing are: (1) the enjoyment of reading the poem enthusiastically; (2) the poem‟s choice of words has made the easy to understand the meaning; (3) the good atmosphere of teaching and learning process; (4) the interaction among them to motivate to write good essay.Based on the finding, it was concluded that literary response approach can improve students‟ analytical essay writing at the second year of English education Department, class E of UIN Suska Riau, therefore, the researcher should continue using these approach in teaching English literature.